Lineage tracing reveals clonal progenitors and long-term persistence of tumor-specific T cells during immune checkpoint blockade - Pai, Joy A; Hellmann, Matthew D; Sauter, Jennifer L; Mattar, Marissa; Rizvi, Hira; Woo, Hyung Jun; Shah, Nisargbhai; Nguyen, Evelyn M; Uddin, Fathema Z; Quintanal-Villalonga, Alvaro; Chan, Joseph M; Manoj, Parvathy; et al. (Cancer cell, 2023)
Paired single-cell RNA and T cell receptor sequencing (scRNA/TCR-seq) has allowed for enhanced resolution of clonal T cell dynamics in cancer. Here, we report a scRNA/TCR-seq analysis of 187,650 T cells from 31 tissue regions, including tumor, adjacent normal tissues, and lymph nodes (LN), from three patients with non-small cell lung cancer after immune checkpoint blockade (ICB). Regions with viable cancer cells are enriched for exhausted CD8 T cells, regulatory CD4 T cells (Treg), and follicular helper CD4 T cells (TFH). Tracking T cell clonotypes across tissues, combined with neoantigen specificity assays, reveals that TFH and tumor-specific exhausted CD8 T cells are clonally linked to TCF7 SELL progenitors in tumor draining LNs, and progressive exhaustion trajectories of CD8 T, Treg, and TFH cells with proximity to the tumor microenvironment. Finally, longitudinal tracking of tumor-specific CD8 and CD4 T cell clones reveals persistence in the peripheral blood for years after ICB therapy.